Effect of Pulsed Injection on Continuous Adductor Block for Postoperative Analgesia after Total Knee Joint Operation - Xiangfeng WANG; Huiqin LUO; Wenzhong TANG; Tingting CHEN; Haojie LU; Guanghui LIU (康复学报)
Objective:To evaluate the analgesic effect of pulsed injection (PI) and constant speed injection (CSI) in continuous adductor block on knee joint postoperative analgesia.Methods:Sixty patients undergoing total knee replacement were randomly divided into PI group and CSI group according to digital table method with 30 cases in each group. Both groups were received continuous femoral nerve block after operation. The prime dose (0.17%ropivacaine+0.2 μg/mL sufentanil) was 10 mL. In the CSI group, continuous dose was started right after prime dose injection, with a background dose of 6 mL/h;in the PI group, the pulse dose was 6 mL/h 60 minutes after prime dose;Both groups were set up PCA 10 mL each time, lock time was 30 minutes. Pain, visual analogue scale (VAS score), muscle strength of quadriceps and recovery index after operation of both groups were recorded at different time points. PCA usage and its complications were also recorded.Results:Compared with those of the CSI group, VAS scores of the PI group were lower when patients accessed at rest or exercise at 12,24,36 and 48 hours after surgery respectively (P<0.05), and there was no significant difference in muscle strength of quadriceps between two groups (P>0.05). The distance of walking, active bending and PCA pressing times of the PI group were significantly better than those of the CSI group (P<0.05). There was no significant difference in postoperative complications between two groups (P>0.05).Conclusion:Pulse injection continuous adductor block would be a more effective analgesic method after knee joint operation, with definite analgesic effect and less complication.